Creep behaviour of injection moulded polyamide 6/organoclay nanocomposites by nanoindentation and cantilever-bending - Seltzer, Rocío (2011)
The creep behaviour of injection moulded PA 6/organoclay nanocomposites was studied by depth-sensing nanoindentation and DMA cantilever-bending. The glass transitions of PA 6 and its nanocomposites were decreased below room temperature upon saturation with water so that the materials could be tested in the rubbery regime. For nanoindentation creep on the skin and core regions of injection moulded samples, whilst organoclay improves the creep resistance of PA 6, the enhancement is due to the decrease of the initial compliance at zero time but the time-dependent creep is actually increased. In contrast, for cantilever-bending creep, organoclay reduces the creep compliance and the time-dependent creep in PA 6. It is suggested that the organoclay imparts a constraint effect on the PA 6 molecular chains, restricting their mobility in the bulk compared to the surface and hence improving their resistance to creep. A modified Halpin–Tsai equation was used to model their creep behaviour under these two loading configurations and compared to experimental data.